African therapy for a fractured world(view): The life of founder bishop Johannes Richmond and the invention of tradition and group cohesion in an African Initiated Church - Wepener, Cas (Hervormde teologiese studies, 2015)
In the book The invention of tradition historian Eric Hobsbawm claims that the process of the invention of tradition serves the formation of group cohesion. The different versions of the life story of the founder bishop of the Corinthian Church of South Africa (AIC), as documented during many years of conducting qualitative field work in this church, are used in this article as a case study in this regard. The article unpacks the way in which the invention of tradition as a process is in this particular AIC currently a work in progress contributing to the formation of a particular type of group cohesion that stretches over racial, religious and denominational boundaries especially by means of the unique liturgical rituals that were influenced by the life story of the founder. The group cohesion that this process fosters is in essence aimed at healing in all its multifaceted dimensions, which includes healing from physical ailments, ‘healing’ from barrenness, healing from spirit possession to healing as (re-)incorporation of an individual into the larger group, the healing of a nation as well as healing from a dualistic spirit-matter worldview.